Process construct in the virtual R&D teams - Ale Ebrahim, N.; Ahmed, S.; Abdul Rashid, S.H.; Taha, Z.; Mohammadjafari, M. (Asia Pacific Industrial Engineering and Management Society, 2012)
literature proves the importance of the process role in the effectiveness of virtual research and development (R&D) teams for new product development (NPD). However, the factors that make process construct in a virtual R&D team are still unclear. The manager of virtual R&D teams for NPD does not know which items of process should be used. To address the gap and answer the question, the study presents a set of factors that make a process construct. The proposed construct modified by finding of the field survey. We empirically examine the relationship between construct, dimensions and its factors by employing the Structural Equation Modeling (SEM). A measurement model built base on the 13 preliminary factors that extracted from literature review. The result shows 9 factors out of 13 factors maintaining to make process construct. These factors can be grouped into two dimensions namely generating report and collaborative system. The findings can help new product development managers of enterprises to concentrate in the main factors for leading an effective virtual R&D team. In addition, it provides a guideline for future research.